Penentuan Kondisi Optimum Ukuran Partikel dan Bilangan Reynold Pada Sintesis Bioplastik Berbasis Sorgum - Yuli Darni (Jurnal Rekayasa Kimia & Lingkungan)
The article reported the laboratory experiment to obtain the optimal condition of particle size and Reynold Number of bioplastic film based on the plastic package standard of High Density Polyethylene (HDPE).  Particle sizes of starch were varied at 63, 90, 106, 600, and 1000 micron, and the mixing rate were changes at 190, 252, 313, 375, and 437 rpm. The concentration of chitosan and gliserol added to solution were set as constant variable as 20 and 10 wt %, respectively. The temperature of gelatinitation was also fixed at 95OC. The fabricated of bioplastic film were characterized for mechanical property such as tensile strength, elongation at break and Modulus Young by using a  Universal Testing Machine. The  morphology of film sheets were observed by using a scanning electron microscopy (SEM). Moreover, the obtained film was also investigated for water uptake parameter. The result showed that the mechanical properties were improve by increasing mixing rate at smallest particle sizes of starch. The water uptakes shows decrease at hight mixing rate. SEM images showed that the morphology of bioplastic was almost simmilar to the morphology of  HDPE.  The optimum condition was found that the best film was obtained at particle size of starch 63 micron, Reynold Number of  959, with mixing rate of  375 rpm. The mechanical value at best condition was 19.27%, 757.046 Mpa, and 142.875 for elongation, Modulus Young,  and tensile strength, respectively.